Quantifying postural control in premanifest and manifest Huntington’s disease using wearable sensors - Porciuncula, Franchino (Neurorehabil Neural Repair, 2020)
BACKGROUND: Impairments in postural control in Huntington’s disease (HD) have important consequences for daily functioning. This observational study systematically examined baseline postural control and the effect of sensory attenuation and sensory enhancement on postural control across the spectrum of HD. METHODS: Participants (N=39) included healthy controls, and individuals in premanifest (pHD) and manifest stages (mHD) of HD. Using wearable sensors, postural control was assessed according to: (1) postural set (sit vs stand); (2) sensory attenuation using clinical test of sensory integration; and (3) sensory enhancement with gaze fixation. Outcomes included sway smoothness, amplitude, and frequency. RESULTS: Based on postural set, pHD reduced postural sway in sitting relative to standing, while mHD had pronounced sway in standing and sitting, highlighting a baseline postural deficit. During sensory attenuation, postural control in pHD deteriorated relative to controls when proprioceptive demands were high (eyes closed on foam), while mHD had significant deterioration of postural control when proprioception was attenuated (eyes open and closed on foam). Finally, gaze fixation improved sway smoothness, amplitude and frequency in pHD; however no benefit was observed in mHD. CONCLUSIONS: Systematic examination of postural control revealed a fundamental postural deficit in mHD, which further deteriorates when proprioception is challenged. Meanwhile, postural deficits in pHD are detectable when proprioceptive challenge is high. Sensory enhancing strategies using gaze fixation to benefit posture may be useful when introduced well before motor diagnosis. These findings encourage further examination of wearable sensors as part of routine clinical assessments in HD.